Imaginando una nación de raza blanca en Costa Rica : 1821-1914 - Ronald Soto Quirós (Les Cahiers ALHIM)
The author tries to demonstrate how in travel literature, commercial reports, projects of colonization, encyclopedias, dictionaries, works of geography, scientific journals of different countries written by diplomats, businessmen, travelers, geographers and naturalists who had visited or who were mentioning information on Costa Rica from the beginning of the XIXth century we can find the construction of a referential library that will serve as base for the consolidation towards ends of the XIXth century of an idea of particular Costa Rican race with singular characters. At the same time, it is an intent to prove how the speech spread by the Costa Rican elites from the middle of the XIXth century also nourished the later interpretations of the foreigners and by the way a differential vision of this country in the Central American and even Latin-American context. Thus, the article tries to underline how the idea of a particular race with white tones was perpetuated being the result of a feedback process between both speeches, although the first documents of the XIXth century mention the existence of a half-caste country.